2015
DOI: 10.1111/1348-0421.12284
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a catalytically inactive cysteine protease domain of RtxA1/MARTXVv as a potential vaccine for Vibrio vulnificus

Abstract: Recent studies have defined several virulence factors as vaccine candidates against Vibrio vulnificus. However, most of these factors have the potential to cause pathogenic effects in the vaccinees or induce incomplete protection. To overcome these drawbacks, a catalytically inactive form, CPD Vv (C3725S), of the well-conserved cysteine protease domain (CPD) of V. vulnificus multifunctional autoprocessing repeats-in-toxin (MARTX Vv /RtxA1) was recombinantly generated and characterized. Notably, active and pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that protective immunity against Vibrio species is induced by both bacterial components and toxins, including LPS, pili, capsular polysaccharides, cholera toxins and MARTX toxins . Among these protective immunogens, MARTX toxins, which comprise a subfamily of large secreted RTX proteins, have been identified in a number of Vibrio species and other pathogenic gram‐negative bacteria .…”
Section: Cross‐reactivity and Cross‐protectivity Of Anti‐rtxa1‐c‐mabsmentioning
confidence: 99%
“…Recent studies have shown that protective immunity against Vibrio species is induced by both bacterial components and toxins, including LPS, pili, capsular polysaccharides, cholera toxins and MARTX toxins . Among these protective immunogens, MARTX toxins, which comprise a subfamily of large secreted RTX proteins, have been identified in a number of Vibrio species and other pathogenic gram‐negative bacteria .…”
Section: Cross‐reactivity and Cross‐protectivity Of Anti‐rtxa1‐c‐mabsmentioning
confidence: 99%
“…Improvement of this rFlaB vaccine will be needed in the future. Flagellin has already been found to have high adjuvant activity [ 19 , 24 ], and therefore should be combined with another additional antigen such as Vibrio vulnificus hemolysin VVH, metalloprotease VvpE, and/or RTX toxin [ 3 , 10 , 13 , 14 , 16 ]. There have been many reports on utilization of these proteins as vaccine antigens, and immunization with these proteins confers effective protection against lethal challenge by V. vulnificus on hosts [ 10 ].…”
mentioning
confidence: 99%